The complete relief of chronic pain utilizing electromagnetic theory: A retrospective observational cohort study - Philip Cornish; Anne Cornish; Jonathan Tuke (iScience)
Summary: We have developed a strategy that has reliably and reproducibly delivered long-term pain-free outcomes to chronic pain patients. This strategy incorporates electromagnetic theory into the use of neuromodulation. We have analyzed the clinical outcome data for 231 of our implanted patients to determine if there is a significant association between the use of our mathematical framework for placing the neuromodulation unit’s electrode array and the state of “pain-free” (PF). There was a statistically significant association between accuracy of electrode array placement and the report of PF (p < 0.00001). The Bayesian logistic regression gave a significant treatment effect on outcome (p = 1.06 × 10−31). Our mathematical framework for the placement of the electrode array of the neuromodulation unit is significantly associated with a pain-free outcome in chronic pain patients.